The 2005 projections of age-related expenditure (2004-50) for the EU-25 Member States: underying assumptions and projection methodologies (Luxembourg, 2006)
"In 2003, the ECOFIN Council gave the Economic Policy Committee (EPC) a mandate to produce a new set of long-run budgetary projections for all twenty-five Member States covering pensions, health care, long-term care, education, unemployment transfers and, if possible, contributions to pensions/social security systems. This follows the projection exercises of 2001 and 2003. The age-related expenditure projections feed into a variety of policy debates at EU level. In particular, they are used in the annual assessment of the sustainability of public finances carried out as part of the Stability and Growth Pact; in the context of the Open-Method of Co-ordination on pensions; and the analysis on the impact of ageing populations on the labour market and potential growth which will be relevant for the Lisbon strategy and Broad Economic Policy Guidelines.